Friends, Foes, and Fringe: Norms and Structure in Political Discussion Networks - Kelly, John; Fisher, Danyel; Smith, Marc A. (Proceedings of the 2006 International Conference on Digital Government Research, 2006)
Online discussion groups have a network structure that emerges from the interactions of thousands of participants, writing in thousands of topical threads. This structure varies greatly according to the type of discussion group, such as technical, fan or support. Political groups have their own distinctive structure, organized around ideologically polarized clusters of participants. Whereas in some other groups, individuals who vehemently disagree with the mainstream might be ignored or ostracized, in political groups most participants preferentially interact with “opponents” and ignore “friends.” And yet, there is a type of opponent whose ideas are so far from the field of debate as to be ignored by most or nearly all other participants. This difference is starkly apparent in network diagrams of discussion groups. The core of highly participative discussants contains opponents from different ideological clusters, tightly bound in debate. But fringe contributors, sometimes called “trolls”, are relegated to peripheral positions by central actors’ lack of interest in responding to their provocations or views. Network visualizations of this phenomenon illustrate how macro-level structure arises and is maintained by micro-level discursive choices.